Visible Light—Responsive Drug Delivery Nanoparticle via Donor–Acceptor Stenhouse Adducts (DASA) - Yap, Jeaniffer E.; Zhang, Lin; Lovegrove, Jordan T.; Beves, Jonathon E.; Stenzel, Martina H. (Macromolecular rapid communications., 2020)
Stimuli‐responsive drug release from a nanocarrier triggered by light enables the control of the amount of drug locally. Here, block copolymer micelles based on poly(ethylene glycol) methyl ether methacrylate (PEGMEMA) as the hydrophilic block and a polymer with pendant donor–acceptor Stenhouse adducts (DASA) are used as a means to trigger the release of drugs under green light. The micelles are loaded with ellipticine to yield light‐responsive nanoparticles with sizes of around 35 nm according to transmission electron microscopy (TEM) analysis. Two micelles with a drug loading content of 4.75 and 7.4 wt% are prepared, but the micelle with the higher drug loading content leads to substantial protein adsorption. The release of ellipticine from the micelle, which is monitored using the polarity‐sensitive fluorescence of ellipticine, can be switched on by light and off by thermal recovery of DASA in the dark. The micelles are readily taken up by Michigan Cancer Foundation‐7 breast cancer cells. Subsequent light irradiation leads to enhanced drug release inside the cell as seen by the enhanced fluorescence. Conjugation of donor–acceptor Stenhouse adducts to block copolymers enables the formation of light‐responsive micelles for drug delivery. The release of the anti‐cancer drug ellipticine can be monitored in vitro as the fluorescence of the drug is quenched inside the micelle, but it is brightly fluorescent after release, which is triggered by green light‐emitting diode light.